Multimodal conservative treatment of migrating bone marrow edema associated with early osteonecrosis of the hip. (February 2022) - Sconza, Cristiano; Coletta, Francesco; Magarelli, Nicola; D'Agostino, Maria Cristina; Egan, Colin Gerard; Di Matteo, Berardo; Respizzi, Stefano; Mazziotti, Gherardo
Bone marrow edema syndrome is a severely disabling painful condition without a defined treatment and related to pathogenetic mechanisms not yet clearly recognized. We report the case of a 59-year-old post-menopausal woman, affected by bone marrow edema associated with early osteonecrosis of the femoral head with secondary appearance of a rare migrant bone edema of the hip acetabulum. Clinical evaluation and magnetic resonance imaging were used to monitor the outcome of the patient. Pre-treatment clinical evaluation revealed pain upon stepping with the left limb, reduced range of motion of spine and hip, and hip pain during passive rotation. Magnetic resonance imaging showed diffuse signal alteration of the head and neck of the left femur in relation to bone edema, associated with an unclear small cephalic area of the femoral head suggestive of initial osteonecrosis. A further computed tomography scan was performed that did not reveal any alterations in bone profile, interruption of the cortex, or trabecular bone collapse. We immediately started a multimodal conservative treatment administering neridronate (100 mg, intravenously) combined with calcium and vitamin D supplementation and biophysical therapies (magnetotherapy and extracorporeal shockwave therapy). We also instructed the patient not to bear the load on the affected lower limb during standing and walking, using crutches. After 2 months, a notable regression of pain with improvement in mobility was observed. Magnetic resonance imaging revealed complete regression of edema at the head and neck of the femur; however, the new appearance of acetabular bone edema of the ipsilateral acetabular roof was detected. After 4 months, a third magnetic resonance imaging showed the disappearance of the femoral head and acetabular roof defects as well as the complete clinical recovery of the patient. An early diagnosis and intervention are essential to conservatively treat cases of bone marrow edema syndrome.